Effects of resistance training frequency on body composition and metabolics and inflammatory markers in overweight postmenopausal women - Orsatti, F. Lera; Nahas, E. A.P. [UNESP]; Maestà, N. [UNESP]; Neto, J. Nahas [UNESP]; Orsatti, C. Lera [UNESP]; Portari, G. Vannucchi; Burini, R. C. [UNESP] (My University, 2014)
The present study aimed to determine the importance of resistance training frequency on body composition and metabolics and inflammatory markers in sedentary overweight postmenopausal women (PW). Thirty subjects finished the resistance training-protocol (60% to 80% of 1-RM) and had all the evaluations (anthropometry, strength, food intake and biochemistry) done. Groups were assembled according to the week-frequency of attended sessions (G1-1 day/ wk, N.=9; G2-2 days/wk, N.=11 and G3-3 days/wk, N.=10). The strength-training protocol resulted in similar changes on body composition and strength gains in all groups. However, the plasma markers responses differed among groups with G1 showing an increase of both CRP and glucose, with G2 increasing CRP and G3 keeping the baseline values. The results suggest that resistance exercise increases strength and muscle mass independently of the frequency. Moreover, highest resistance training frequency (3 days/week) prevented the rise of plasma glucose and CRP profile after 16 weeks of training in sedentary overweight PW.
Keywords: Insulin resistance; Muscles; Resistance training